South Africa’s Basic Education Curriculum and Social Transformation of Learners in Underdeveloped Communities - Magcayi, Sincedise (University of the Witwatersrand, Johannesburg, 2022)
Several studies on curriculum and social transformation in the basic education sector indicate that there is inadequate research on how education, through curriculum policy, can be instrumental in fostering social change among learners from underdeveloped communities. This research explored education policy and its contribution to social transformation, looking into ways in which teachers teach civic values to children in underdeveloped settings. Making use of qualitative research methods the study engaged with Life Skills (LS) and Life Orientation (LO) teachers from Phumelela Primary School based in Sicelo community of Meyerton in Gauteng, as a case study to understand the effect of South Africa‟s education policy in fostering social transformation through the curriculum. A total of fourteen LS and LO teachers were sampled to participate in focus group discussion as means to obtain primary data around the subject. Research findings indicate that varying pedagogies are being used by teachers to transmit civic values such as respect, social cohesion and morality. However, these are not easy to coordinate because of the complexity of the learning environment and backgrounds that learners emanate from. Instead, pedagogic strategies can be used conditionally as learners are different. While teachers use pedagogies in their teachings, government and local communities remain key stakeholders that need to assist in the teaching of civic values, and in the social transformation process of learners.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Civic values; Social transformation; Curriculum; UCTD; SDG-4: Quality education